2011
DOI: 10.1007/s11104-011-0991-8
|View full text |Cite
|
Sign up to set email alerts
|

Induction of metabolite organic compounds by mutualistic endophytic fungi to reduce the greenhouse whitefly Trialeurodes vaporariorum (Westwood) infection on tomato

Abstract: Background and aims Six mutualistic endophytic fungi that are known to colonize the endorhiza have shown biological control properties against plant-parasitic nematodes. In this study we aim to investigate the potential of these endophytic fungi to reduce the phloemfeeding insect Trialeurodes vaporariorum (Westwood) on tomato. Methods To determine the host plant choice of T. vaporariorum, the total number of insects present on each plant was counted daily for 10 days, and then the second leaf below the shoot a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 50 publications
1
26
1
Order By: Relevance
“…; Newcombe, Martin & Kohler ; Menjivar et al . ; Zhang et al . ), although these effects can also be influenced by nutrients and other biotic factors (Saikkonen et al .…”
Section: Invasive Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Newcombe, Martin & Kohler ; Menjivar et al . ; Zhang et al . ), although these effects can also be influenced by nutrients and other biotic factors (Saikkonen et al .…”
Section: Invasive Plantsmentioning
confidence: 99%
“…Some endophytes have been shown to increase invasive plant species fitness (Clay 1988;Rudgers, Koslow & Clay 2004;Aschehoug et al 2012). While endophytes can confer many different benefits, research has frequently shown negative effects of endophytes on mammalian and insect herbivores (Raps & Vidal 1998;Jallow, Dugassa-Gobena & Vidal 2004;Clay, Holah & Rudgers 2005;Rudgers & Clay 2008;Vega et al 2008;Newcombe, Martin & Kohler 2010;Menjivar et al 2012;Zhang et al 2012), although these effects can also be influenced by nutrients and other biotic factors (Saikkonen et al 2006;Eschen et al 2010). In some cases, the negative effects of endophytes on herbivores can be passed on to the second generation of herbivoreseven if they are not feeding on the endophyteinfected host plant (Jaber & Vidal 2010)or onto predators or parasitoids of the herbivores (de Sassi, Muller & Krauss 2006;Harri, Krauss & Muller 2008b) or even hyperparasitoids (Harri, Krauss & Muller 2008a).…”
Section: Invasive Plants C a N P M I I N T E R A C T I O N S P R O M mentioning
confidence: 99%
“…), less (Kruess , Laine , Menjivar et al. ) or as attractive as not challenged plants (Jallow et al. , Spafford Jacob et al.…”
Section: Introductionmentioning
confidence: 99%
“…Although largely ignored until recently (Porras-Alfaro & Bayman, 2011;Wani et al, 2015), a growing number of studies demonstrate that the presence of these facultative endophytes in the plant can be manipulated in both mono-and dicots through the targeted inoculation of candidate fungi. These endophytecolonized plants can negatively affect the performance and survival of a range of both above-and below-ground herbivores (e.g., Gurulingappa et al, 2010;Hernawati et al, 2011;Akello & Sikora, 2012;Menjivar et al, 2012;Gange et al, 2012;Martinuz et al, 2013;Thakur et al, 2013;Akutse et al, 2013;Batta, 2013;Lopez et al, 2014;Lopez & Sword, 2015;Zhou et al, 2016a,b). Facultative fungal endophytes can also be involved in nutrient transfer to plants, and positively affect plant growth, thereby potentially serving as multifaceted tools for plant protection and health in agricultural systems (Behie et al, 2012;Behie & Bidochka, 2014;Barelli et al, 2016;Jaber & Enkerli, 2016;Lugtenberg et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Facultative fungal endophytes have been shown to affect the feeding behavior and performance of a wide range of insect herbivores from different feeding guilds with varying effects (Hartley & Gange, 2009;Gange et al, 2012) including phloem-feeders such as aphids and whiteflies (Hernawati et al, 2011;Akello & Sikora, 2012;Menjivar et al, 2012;Lopez et al, 2014;Zhou et al, 2016a,b), dipterans (Akutse et al, 2013), beetles (Newcombe et al, 2009;Biswas et al, 2013), caterpillars (Bing & Lewis, 1992;Lopez & Sword, 2015;Thakur et al, 2013;Batta, 2013;Zhou et al, 2016a,b), grasshoppers (Gurulingappa et al, 2010, and hymenopteran gall wasps (Quesada-Moraga et al, 2009). Notably missing from these examples are negative effects of facultative fungal endophytes on the true bugs (Hemiptera: suborder Heteroptera).…”
Section: Introductionmentioning
confidence: 99%